Peran Media Sosial Dalam Meningkatkan Brand Loyalty Di Kalangan Milenial Dan Gen Z - rahmadhani, Linda; Khofi Inayah , Maulida; Liana, Lia; Mirzaq; Tija, Irmansyah (LPPM STIA Lancang Kuning Dumai, 2025)
The development of information and communication technology has brought major changes in various aspects of life, including in the way brands communicate with consumers. One significant change is the emergence of social media as a platform that connects brands with consumers directly. Social media such as Instagram, TikTok, Twitter, and YouTube are not only communication tools but also strategic media for building close relationships between brands and consumers. This is especially relevant in reaching the millennial generation and Gen Z, who are known as digital natives because of their habits of being attached to the digital world (Smith, 2020). In this context, social media is not only a promotional tool but also a medium for building sustainable relationships, which ultimately can increase brand loyalty. However, while social media offers great opportunities, there are challenges that brands must overcome, such as how to create consistent and relevant content and maintain authentic interactions amidst increasing competition. Therefore, this research aims to explore the role of social media in increasing brand loyalty among millennials and Gen Z by highlighting strategic aspects such as engagement, creative content, and user experience.